The economy fifty years since martial law: Changing landscapes, unchanged views - Emmanuel S. De Dios (University of the Philippines, School of Economics (UPSE), 2022)
The five decades that have passed since Marcos declared martial law is an opportunity for stocktaking relative to the present. This piece is a summary comparison of the character of the economy that existed under the Marcos regime and the current structure and problems experienced by the post-millennial economy. The stark differences described are unfortunately still not fully reflected in current economic discussions, a good part of which is still preoccupied with issues pertaining to a vanishing past. This prevents the country from confronting its real problems and exploiting new opportunities.
Keywords: N15; O53; 330; martial law; Marcos; services economy; business-process outsourcing; overseas remittances; Philippine development strategies; protectionism and liberalisation